STRATEGI KOMUNIKASI ANTI NARKOBA DALAM LITERASI MEDIA DI INDONESIA - sa, lisa; Utami, Atikah Dewi (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2022)
The State of Indonesia is currently facing a "Narcotics Emergency". The prevalence rate for the past year regarding drug abuse has increased from 1.80 percent in 2019 to 1.95 percent in 2021. This means that 180 out of 10,000 Indonesian residents aged 15-64 years have been exposed to drug use in the past year. In order to overcome this problem, it is necessary to increase understanding of the dangers of narcotics and various regulations for dealing with narcotics in Indonesia. This article aims to explain the various media regulations in building a "shining" drug-clean generation. In this case the author uses a descriptive study by telling a phenomenon that clearly describes the problem of drug abuse that has occurred in Indonesia. Furthermore, it is analyzed to obtain results that are used in order to understand phenomena about what is happening in our country which tends to have an impact on life subjects such as behavior, perceptions, motivations, actions and others. The results of this paper show that there is an introduction strategy that the media builds our picture and understanding of the social world. The media has become our story tellers about the social world, the media are also our entertainers and in particular the media has an impact on us. The concept of "media literacy" is an alternative to empowering the community in the midst of a massive onslaught of news from the media on the dangers of drugs.